Vertical annular flow characteristics for air/silicone oil system - Al-Aufi, Yousuf Abdullah (2018)
Annular flow is one of the most common two-phase flow regimes observed in industrial applications. In annular flow, the liquid flows partly as a thin film along the pipe wall and partly as droplets entrained in the turbulent gas core. Most of the previous studies about the characteristics of annular flow and the developed correlations were conducted using an air/water system. This thesis reports an investigation about the characteristics of the annular flow regime and a development of liquid film thickness measurement using an ultrasonic technique in air/water and air/silicone oil systems.